(untitled) (Third Sector Social Economic Review, 2012)
In this study, effects of factors causing stress for instuctors on performance levels are discussed. Examples of the study have been chosen among 350 instuctors in Gazi Univesity. In the research, factors causing stress on instuctors’ performance are determined and their performance at the time of stress are analyzed and the effects of factors causing stress on their performances are determined according to their status. At the end of theresearch, it is concluded that among instuctors, there is no statistacally appearant difference between factors causing stress and their performances for ones having status of research associate, specialist-lecturer andacamedician. Beside this for ones having status of Assistant Professor, Associate Professor and Professor there appeared to be a statistical difference between factors causing stress and their performances.